Efficacy and safety during formulation switch of a pasteurized VWF/FVIII concentrate: results from an Italian prospective observational study in patients with von Willebrand disease. (7th September 2012) - Castaman, G.; Coppola, A.; Zanon, E.; Boeri, E.; Musso, M.; Siragusa, S.; Federici, A. B.; Mancuso, G.; Barillari, G.; Biasoli, C.; Feola, G.; Franchini, M.; et al.
Summary Von Willebrand disease (VWD) is an inherited bleeding disorder caused by the quantitative or qualitative deficiency of von Willebrand factor (VWF). Replacement therapy with plasma‐derived VWF/factor VIII (FVIII) concentrates is required in patients unresponsive to desmopressin. To assess the efficacy, safety and ease of use of a new, volume‐reduced (VR) formulation of VWF/FVIII concentrate Haemate® P in patients requiring treatment for bleeding or prophylaxis for recurrent bleeding or for invasive procedures. Pharmacoeconomic variables were also recorded. Data were analysed using descriptive statistics. This was a multicentre, prospective, observational study. Consecutively enrolled patients received Haemate®PVR according to their needs, and were followed for 24 months. Of the 121 patients enrolled, 25.6% had type 3 VWD and more than 40% had severe disease. All patients were followed for 2 years, for a total of 521 visits. On‐demand treatment was given to 61.9% of patients, secondary long‐term prophylaxis to 25.6% and prophylaxis for surgery, dental or invasive procedures to 45.5%. The response to treatment was rated as good to excellent in >93–99% of interventions. The new formulation was well tolerated by all patients with no report of drug‐related adverse events. The switch to volume‐reduced Haemate® P was easy to perform and infusion duration was decreased twofold compared with the previous formulation. Volume‐reduced Haemate® P was at least as effective and well‐tolerated as the previous formulation.